P016 Evaluating the effectiveness of an interactive educational intervention on sleep health for second-year pharmacy students. (9th November 2022) - Basheti, M; Bussing, J; Grunstein, R; Gordon, C; Saini, B
Abstract: Background: Pharmacists are usually the most frequently consulted professionals in primary care for health concerns, such as sleep disturbances. However, conventionally, curricular space devoted to sleep health has been insufficient and this eventuates in suboptimal care provision. For example, pharmacists often provide over the counter/complementary medicines rather than the recommended behavioural counselling for insomnia management. Clearly, pedagogically informed learning experiences about sleep health/insomnia management are important to improve practice. Objectives: To develop, implement and evaluate an interactive sleep health educational intervention for 2nd year pharmacy students. Methods: An educational intervention utilising a flipped classroom approach, with interactive lectures, self-reflection around personal sleep habits, and role-playing behavioural treatment provision was designed and implemented. A questionnaire assessing pre- and post-intervention changes in knowledge about and attitudes towards sleep as well as post-intervention learning satisfaction, was administered to students. Results: Mean total knowledge scores for participating students (n=125, 70.4% females) improved significantly post-intervention from a baseline of 11.1 ± 3.8 to 17.1 ± 3.5 post-intervention, p <0.05 (Score range= 0-25). The mean total attitudes scores also improved from 28.8 ± 3.2 at baseline to 29.4 ± 3.8 (Score range= 10-50), p=0.07; however, this change was insignificant. Conclusion: Carefully crafted educational interventions for pharmacy students can help improve sleep health knowledge. Whilst a trend to improved sleep health attitudes was evident, it was not significant, possibly because of positive sleep health attitudes even at baseline. Such programs should be incorporated into pharmacy pre-registration curricula to potentially enhance future pharmacists' skills in sleep health provision.